Description of the First Four Species of the Genus Pseudogymnoascus From Antarctica - Villanueva, Pablo; Vásquez, Ghislaine; Gil-Durán, Carlos; Oliva, Vicente; Díaz, Anaí; Henríquez, Marlene; Álvarez, Eduardo; Laich, Federico; Chávez, Renato; Vaca, Inmaculada (Frontiers in Microbiology, 2021)
The genus Pseudogymnoascus represents a diverse group of fungi widely distributed in different cold regions on Earth. Our current knowledge of the species of Pseudogymnoascus is still very limited. Currently, there are only 15 accepted species of Pseudogymnoascus that have been isolated from different environments in the Northern Hemisphere. In contrast, species of Pseudogymnoascus from the Southern Hemisphere have not yet been described. In this work, we characterized four fungal strains obtained from Antarctic marine sponges. Based on multilocus phylogenetic analyses and morphological characterizations, we determined that these strains are new species, for which the names Pseudogymnoascus antarcticus sp. nov., Pseudogymnoascus australis sp. nov., Pseudogymnoascus griseus sp. nov., and Pseudogymnoascus lanuginosus sp. nov. are proposed. Phylogenetic analyses indicate that the new species form distinct lineages separated from other species of Pseudogymnoascus with strong support. The new species do not form sexual structures and differ from the currently known species mainly in the shape and size of their conidia, the presence of chains of arthroconidia, and the appearance of their colonies. This is the ﬁrst report of new species of Pseudogymnoascus not only from Antarctica but also from the Southern Hemisphere.